Linking exchange rates, market failures and agricultural land demand - Jamal Othman, (Penerbit Universiti Kebangsaan Malaysia, 2000)
The financial crisis of 1997/98 has provided the so-called "Sun set" agricultural sector a rejuvenated role as a growth impetus. This leads to concerns as to whether agricultural augmentation would pose significant repercussions on the pattern of naruml resource use, especially land factor. This paper explores whether sustained depreciation of The Malaysian Ringgit will pose significant impacts on agricultural land demand in the country, with special focus on the oil palm sub-sector. A comparative static, single commodity model with explicit land factor is employed. Analysis shows that a prolonged Ringgit depreciation of 40 percent ceteris paribus will have substantial impacts on land demand (about 10 percent for the oil palm sub-sector). In reality, expansion of oil palm land-use could be greater as other crops, especially rubber is steadily being converted to oil palm due to relative commodity price changes and rising production cost.